Application of Choice Learning Method in Early Childhood Decision Making - Saskia Fayza Paramita; Azi Matur Rahmi (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
Decision-making ability is an important aspect that needs to be developed from an early age because it plays a role in the formation of independence, responsibility, and self-confidence in children. This study aims to describe the application of the Choice Learning method in developing decision-making abilities in early childhood at Rainbow Kids Kindergarten. The study used a descriptive qualitative approach with the principal, class teachers, and children in group B as subjects. Data were collected through observation, interviews, and documentation. The results showed that the Choice Learning method was implemented by providing freedom to choose learning activities, opportunities to try new things, and habituating responsibility for the choices made. This approach has a positive impact on children's decision-making abilities, as seen from the increased courage to choose, self-confidence, independence, and responsibility in completing activities. Thus, Choice Learning effectively supports the development of decision-making abilities and the social-emotional development of early childhood.